FIGURE 5 in Ranunculus schmalhausenii (section Batrachium, Ranunculaceae), a neglected water crowfoot endemic to Fennoscandia-a case of rapid hybrid speciation in postglacial environment of North Europe - Bobrov, Alexander A.; Zalewska-Gałosz, Joanna; Jopek, Magdalena; Movergoz, Ekaterina A. (Zenodo, 2015)
FIGURE 5. Herbarium specimens (H) of Ranunculus schmalhausenii of different morphotypes: A—typical lake form (Russia, Murmansk region, lake Notozero, H 801405), B—typical river form (Finland, Kittilä Lapland, Ylikylä, H 801383), C—form with lobed petals (Finland, Finland proper, Jalassaari, H 801409), D—form with many petaled flowers (Finland, South Häme, lake Norijärvi, H 043172). Published as part of Bobrov, Alexander A., Zalewska-Gałosz, Joanna, Jopek, Magdalena & Movergoz, Ekaterina A., 2015, Ranunculus schmalhausenii (section Batrachium, Ranunculaceae), a neglected water crowfoot endemic to Fennoscandia-a case of rapid hybrid speciation in postglacial environment of North Europe, pp. 101-138 in Phytotaxa 233 (2) on page 122, DOI:10.11646/phytotaxa.233.2.1, http://zenodo.org/record/13633301